2009
DOI: 10.1016/j.jcrs.2009.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis for residual refractive errors after apodized diffractive multifocal intraocular lens implantation

Abstract: Laser in situ keratomileusis for residual ametropia after apodized diffractive multifocal IOL implantation was predictable, effective, and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…Six months after LASIK, 100% of the eyes were within G1.0 D of the target and 96.2% were within G0.5 D. All eyes achieved a UDVA of 20/30 or better, and no patient lost more than 1 line of CDVA. 50 In 2009, Muftuoglu et al 51 validated the findings of Alfonso et al in a retrospective study of 85 eyes of 59 patients with pseudophakic myopic, mixed astigmatic, and hyperopic refractive error after implantation of a diffractive multifocal IOL. Laser in situ keratomileusis was performed with the Intralase FS-60 and Visx Star in patients with a mean age of 61 years, SE refractions ranging from À2.58 to C1.63 D, and astigmatism as high as 3.00 D. At 6 months, 99% of the eyes were within G1.0 D of emmetropia and 96% were within G0.5 D of emmetropia; 98% of eyes had 1.0 D or less of astigmatism.…”
Section: Laser Vision Correction After Implantation Of a Multifocal Imentioning
confidence: 77%
See 1 more Smart Citation
“…Six months after LASIK, 100% of the eyes were within G1.0 D of the target and 96.2% were within G0.5 D. All eyes achieved a UDVA of 20/30 or better, and no patient lost more than 1 line of CDVA. 50 In 2009, Muftuoglu et al 51 validated the findings of Alfonso et al in a retrospective study of 85 eyes of 59 patients with pseudophakic myopic, mixed astigmatic, and hyperopic refractive error after implantation of a diffractive multifocal IOL. Laser in situ keratomileusis was performed with the Intralase FS-60 and Visx Star in patients with a mean age of 61 years, SE refractions ranging from À2.58 to C1.63 D, and astigmatism as high as 3.00 D. At 6 months, 99% of the eyes were within G1.0 D of emmetropia and 96% were within G0.5 D of emmetropia; 98% of eyes had 1.0 D or less of astigmatism.…”
Section: Laser Vision Correction After Implantation Of a Multifocal Imentioning
confidence: 77%
“…Refractions remained stable over 6 months, and 86% had a UDVA of 20/25 or better and an uncorrected near visual acuity (UNVA) of Jaeger 1 or better concurrently; no patient lost more than 1 line of CDVA. 51 Fifteen percent of the cohort (13 of 85 eyes) studied by Muftuoglu et al 51 had wavefront-guided treatment with iris registration. The authors observed no significant differences between wavefront-guided and conventional LASIK for the parameters of refraction, UDVA, and UNVA.…”
Section: Laser Vision Correction After Implantation Of a Multifocal Imentioning
confidence: 99%
“…These findings show that LRIs were effective in reducing astigmatism. However, given the chance that in the future these patients will have LASIK that has good outcomes, 15 it may be reasonable to refrain from placing LRIs at the time of surgery in cases of higher astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the 150-kHz iFS advanced femtosecond laser has the highest repetition rates among the products of AMO Inc., their 60-kHz FS60 laser is the most popular machine worldwide. 3,24,[48][49][50] Due to this reason, we simulated the temperature increase for the 60-kHz FS60 laser using pulse energy 1.6 μJ. In addition, we also modeled the temperature increase for two other systems: we used 1.4-μJ laser pulse energy for the 40-kHz FEMTEC system and 0.3-μJ laser pulse energy for the 200-kHz VisuMax system.…”
Section: -Khz Repetition Rate Is Shown In the Inset Ofmentioning
confidence: 99%